Education as a Positional Good? Evidence from the German Socio-Economic Panel - Alessa K. Durst (Social Indicators Research, 2021)
People care about their relative standing in society and therefore compare themselves to relevant others. Empirical findings suggest that there are concerns for relative standing for different goods and life domains such as income, cars, attractiveness, and supervisor's praise. Even education has been mentioned as having a (partially) positional character. However, there has been only small consideration of education as a positional good in the empirical literature so far. Based on the literature on positional concerns and the role of education on relative position, I use German panel data to investigate the relationship between education and life satisfaction beyond the effect education might have through other variables such as income, health, or occupational prestige. Additionally, I consider the possibility that the consumption of education is subject to positional concerns. I discover a positive relationship between education and life satisfaction, indicating that education has a consumption component. Moreover, the relationship depends on the distribution of particular levels of education, suggesting that education has a positional character.
Keywords: I21; I31; Z13; 300; Education; Positional good; Subjective well-being; Germany